Challenges in Equipping Learners for the Fourth Industrial Revolution: School Leaders’ and Teachers’ Powerlessness - Mlangeni, Ntombenhle Sylvia; Seyama-Mokhaneli, Sadi (Research in Social Sciences and Technology, 2024)
The work landscape is evolving with the advent of the Fourth Industrial Revolution (4IR), potentially rendering current jobs obsolete and necessitating new skills or retraining of existing occupations for future employment. This revolution is disrupting nearly every sector, including education, highlighting the need for education to address issues like unemployment, poverty, and inequality. However, to adequately prepare learners, this can only be achieved with sufficient material and human resources. Understanding these dynamics is crucial in determining whether school leaders and teachers possess the power or autonomy to develop the necessary knowledge, skills, and competencies to empower learners for the 4IR. Power, the ability to achieve organizational objectives, is essential for school leaders and teachers responsible for information and communication technologies in schools to acquire the resources and competencies needed for the 4IR. Drawing on critical theory, this qualitative study explores how school leaders and teachers experience powerlessness due to the challenges they encounter in preparing learners for the 4IR. Semi-structured interviews facilitated participants’ reflections and meaning-making of their experiences in this regard. The critical analysis of data yielded themes that underscore the complexities of preparing learners for the 4IR in underserved contexts ill-equipped for such endeavours: time constraints; teacher uncertainty; insufficient infrastructure, incapacitating influence of powerful top management; and detrimental control of district circuits. Participants felt constrained within their job descriptions, lacked the freedom to exert authority over their work, and faced obstacles in making independent decisions and implementing necessary changes.